Natural Fibre-Reinforced Biofoams - Anne Bergeret; Jean Charles Benezet (International Journal of Polymer Science)
Starches and polylactic acids (PLAs) represent the main biobased and biodegradable polymers with potential industrial availability in the next decades for “bio” foams applications. This paper investigates the improvement of their morphology and properties through processing and materials parameters. Starch foams were obtained by melt extrusion in which water is used as blowing agent. The incorporation of natural fibres (hemp, cellulose, cotton linter, sugarcane, coconut) in the starch foam induced a density reduction up to 33%, a decrease in water absorption, and an increase in mechanical properties according to the fibre content and nature. PLA foams were obtained through single-screw extrusion using of a chemical blowing agent that decomposed at the PLA melting temperature. A void content of 48% for PLA and 25% for cellulose fibre-reinforced PLA foams and an improvement in mechanical properties were achieved. The influence of a fibre surface treatment was investigated for both foams.